Loss of alpha power is related to increased gamma synchronization-A marker of reduced inhibition in tinnitus? - Lorenz, Isabel; Müller, Nadia; Schlee, Winfried; Hartmann, Thomas; Weisz, Nathan (Neuroscience Letters, 2009)
Tinnitus is the perception of sound in the absence of any external auditory stimulus. Based on previous research we have proposed a framework which postulates that the reduction of ongoing inhibitory alpha activity in tinnitus subjects favors a synchronization of neurons in the gamma frequency range while in a resting state. In the present work we are validating the existence of an inverse relationship between auditory gamma and alpha activity in tinnitus and control subjects using Magnetoencephalography. Tinnitus subjects exhibited a significantly steeper slope of the regression line compared to controls, presumably because a greater number of subjects concurrently exhibited low alpha and high gamma power. Therefore, the role of the alpha-gamma pattern is discussed regarding its possible implication for the generation of tinnitus. © 2009 Elsevier Ireland Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Alpha; Gamma; Magnetoencephalography; Oscillatory brain activity; Tinnitus